Pengaruh Model Pembelajaran Problem Based Learning (PBL) Berbasis Praktikum Terhadap Kemampuan Berpikir Kritis Siswa Kelas VIII Pada Pembelajaran IPA di SMP Negeri 9 Jember - I Ketut Mahardika; Ni’matun Nailil Izza; Wahyu Dharmawan; Amellia Lailatun Nisa (Peneliti.net, 2022)
This study aims to improve students' critical thinking skills through the Problem Based Learning (PBL) learning model in science subjects at SMP Negeri 9 Jember. The sample of this research was class VIII students of SMP Negeri 9 Jember as the recipients of the action, Science teachers at SMP Negeri 9 Jember as the subject of the action, and the researcher as the subject who made the observations. Methods of data collection carried out by researchers through interviews, observation, and experiments. The results of the study showed that there were differences in students' critical thinking skills in natural science learning on digestion using the practicum-based Problem Based Learning (PBL) model with groups of students using conventional learning models. So it can be concluded that the practicum-based Problem Based Learning (PBL) learning model can improve the critical thinking skills of class VIII students in science learning at SMP Negeri 9 Jember.